Data analysis and taxonomic management in professional information activities - Moreiro-González, José-Antonio (Anuario ThinkEPI, 2023)
Job postings in the Library and Information Science (LIS) sector increasingly include information professionals on teams that analyze data and organize it into knowledge organization systems (KOS). This involves processing and visualizing the data of businesses and organizations on the basis of their capacity to prepare and analyze data and fit into multidisciplinary research teams. To organize the results of data analysis, products and other content objects use KOS, in particular website taxonomies. The taxonomists´ task is not limited to coordinating and categorizing, as they take part in the entire process of analysis, management, and preparation for data consultation.
Keywords: Data analysis; Data organization; Knowledge organization systems; Taxonomies; Profiles of information professionals; Digital taxonomists